(untitled) (Annals of Medical Research, 2023)
Aim: In our study, we aimed to examine the relationship between laboratory tests with sleep and quality of life in patients using depot antipsychotics as monotherapy for the last three months. Materials and Methods: Patients with schizophrenia and receiving monotherapy depot antipsychotic form were included in our study. Calgary Depression in Schizophrenia Scale (CSS), Positive and Negative Syndrome Scale (PANSS), Pitssburg Sleep Quality Index (PUKİ), Scale of Short Form-36 (SF-36) were administered. The laboratory parameters of the participants were evaluated. Results: Sixty one to study; 80.3% male and 19.7% female patients were included. The mean age of all patients was 36.40±9.96, and the mean body mass index was 24.49±5.18. There was no significant difference between the groups in terms of PSQI subscales and total scores (p>0.05). Only the social functioning score for SF-36 was worse than the other two groups of patients using zuclopenthixol depot (p=0.049). There was no difference between the groups in SF-36 other subscale scores (p<0.05). Prolactin value and other laboratory parameters were also not different between groups (p>0.05). Conclusion: Based on the results we have obtained, general functionality levels such as sleep and quality of life of the patients should be considered while determining the depot antipsychotic forms. In order to generalize and interpret the findings of our study, there is a need to conduct studies involving larger sample groups and different periods of the disease.